2019
DOI: 10.32615/ps.2019.055
|View full text |Cite
|
Sign up to set email alerts
|

Seed priming with calcium chloride improves the photosynthesis performance of faba bean plants subjected to cadmium stress

Abstract: Faba bean (Vicia faba L.) seeds were treated with H2O [nonprimed (NP)] or 2% CaCl2 [primed (P)] before germination for 6 h. After seven days, seedlings were exposed to 0 or 50 µM CdCl2 concentrations for three weeks. Under Cd treatment, P plants showed an improvement of gas-exchange characteristics, chlorophyll (Chl) and carotenoids contents as compared to NP plants subjected to Cd stress. Additionally, the values of Chl fluorescence were relatively similar to those of control, implying that no photodamage occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 57 publications
0
10
0
Order By: Relevance
“…Salinity is one of the major obstacles to increasing crop production worldwide. It becomes the principal abiotic stress that negatively affects faba bean during the vegetative and reproductive phases and definitely at grain production (Ali et al 2013, Nouairi et al 2019. The data of our study showed wide genotypic differences in response to salinity (Fig.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Salinity is one of the major obstacles to increasing crop production worldwide. It becomes the principal abiotic stress that negatively affects faba bean during the vegetative and reproductive phases and definitely at grain production (Ali et al 2013, Nouairi et al 2019. The data of our study showed wide genotypic differences in response to salinity (Fig.…”
Section: Discussionmentioning
confidence: 49%
“…These problems contribute to ionic imbalance, the closing of stomata, and reduction in the photosynthetic enzymatic process which affects the growth of the plant (Semida et al 2014). Therefore, the decrease in plant growth might be due to salinity-induced toxicity on photosynthetic apparatus and structural alterations in plants (Nouairi et al 2019). According to our results, tolerant faba bean genotypes were capable to conserve their photosynthesis and biomass and therefore surmount salinity conditions.…”
Section: Discussionmentioning
confidence: 53%
“…The plant pigments, including chlorophyll, carotenoids contents were measured as described in previous studies [ 9 , 61 , 62 ] with simple modifications. In brief, 0.1 g fresh leaf was soaked in 15 ml extracting solution and then shook with 50 rpm/min for 24 h under dark condition.…”
Section: Methodsmentioning
confidence: 99%
“…Slow crop emergence and seedling growth increase the risk of pests and delay crop performance, which adversely affects seed yield. Previous research showed that seed priming with various substances improved faba bean performance under stress conditions [27][28][29]. However, the effect of hydro-priming on faba bean germination and emergence has not been examined, especially under field conditions.…”
mentioning
confidence: 99%